Self-Calibration Highly Sensitive Photonic Crystal Fiber Biosensor - Mohamed Farhat O. Hameed; Yassmin K. A. Alrayk; S. S. A. Obayya (IEEE Photonics Journal, 2016)
A novel design of a highly sensitive self-calibration biosensor based on a surface plasmon photonic crystal fiber is presented and analyzed using a full-vectorial finite-element method. In this paper, the sensor geometrical parameters are optimized to achieve high sensitivity for the two polarized modes. The numerical results reveal that the resonant peaks corresponding to the two polarized beams are highly sensitive to the variation of the analyte refractive index. Therefore, high refractive index sensitivity of about 6700 nm/refractive index unit (RIU) and 10 000 nm/RIU with the corresponding resolution of $1.49× 10^{-5}$ and $1.0× 10^{-5}$ RIU can be obtained according to the quasi-transverse magnetic (TM) and quasi-transverse electric (TE) modes, respectively. Additionally, the reported self-calibration biosensor has high linearity and high accuracy. Furthermore, the suggested biosensor has great potential for biological and biochemical analytes detection.